Law and Religion in Contemporary Society: Communities, Individualism and the State - Edge, Peter W. (Taylor and Francis, 2000)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- List of Contributors -- Introduction -- Part 1: Context -- 1 Religion and Law in Great Britain at the End of the Second Christian Millennium -- 2 Neutrality between Religions or Neutrality between Religion and Non-religion? -- Part 2: Religious Organisations and the State -- 3 Equity, Inclusivity and Participation in a Plural Society: Challenging the Establishment of the Church of England -- 4 Religious Organisations and the Human Rights Act 1998 -- Part 3: Communalism in the Law -- 5 Children's Religious Freedom, Devout Parents and the State -- 6 Sacred Spaces and Planning Law: Property Rights and the Regulation of Religious Activities in the United States -- 7 Knowledge, Negotiation and NAGPRA: Reconceptualizing Repatriation Discourse(s) -- 8 The Employment of Religious Adherents by Religious Organisations -- Part 4: Conclusion -- 9 Religion, Law and Human Rights: Locating the Debate -- Index